The hygienic standards of xenobiotics in different environments as a unified system - M. R. Gzhegotsky; B. M. Shtabsky; L. M. Shafran; W. Zukow (Kazimierz Wielki University, 2015)
Gzhegotsky M. R., Shtabsky B. M., Shafran L. M., Zukow W. The hygienic standards of xenobiotics in different environments as a unified system. Journal of Education, Health and Sport. 2015;5(1):31-40. ISSN 2391-8306. DOI: 10.13140/2.1.2725.1523 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A31-40 https://pbn.nauka.gov.pl/works/521632 http://dx.doi.org/10.13140/2.1.2725.1523 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. Conflict of interest: None Conflict of interest declared. Received: 15.06.2014. Revised 05.10.2014. Accepted: 25.12.2014.   the hygienic standards of xenobiotics in different environments AS A UNIFIED SYSTEM   M. R. Gzhegotsky*, B. M. Shtabsky*, L. M. Shafran**, W. Zukow***   *Danylo Galytsky Lviv National Medical University, Lviv, Ukraine **Ukrainian Scientific and Research Institute of Transport Medicine, Odessa, Ukraine ***Kazimierz Wielki University, Bydgoszcz, Poland   Ключевые слова: химические вещества, гигиенические нормативы, надежность, нормирование, системный подход, кумулятивная токсичность, использование при регламентации.   Keywords: chemicals, hygienic standards, the reliability, standardization, system approach, cumulative toxicity.   Słowa kluczowe: substancje chemiczne, standardy higieniczne, niezawodność, standaryzacja, podejścia systemowego, skumulowanej toksyczności, stosowanie standaryzacji.   Резюме   Cистемный подход к гигиеническому нормированию ксенобиотиков в разных средах   М. Р. Гжегоцкий, Б. М. Штабский, Л. М. Шафран, W. Zukow   На основе собственных экспериментальных данных и комплексного анализа национальных показателей токсикометрии и ПДК 330 химических веществ в разных средах, а также 265 нормативов, используемых в США и ЕЭС, разработан и внедрен системный подход для обоснования гигиенических нормативов химических веществ в разных средах. Он предполагает учет параметров токсичности и кумулятивных свойств нормируемых веществ, которые интегрально проявляются в величине надежности норматива, определяемой по соотношению LC50(LD50)/ПДКрз, что коррелирует с соответствующими  соотношениями зарубежных нормативов. При этом аргументировано использование ПДКрз как системообразующего показателя. Внедрение разработанных авторами и утвержденных Минздравом Украины Методических указаний открыло возможности для существенного снижения степени неопределенности в процессе гигиенического нормирования, повышения надежности разрабатываемых новых и коррекции существующих нормативов на основе вновь накопленных экспериментальных и клинических данных. Дальнейшее развитие системного подхода в гигиеническом нормировании позволит более успешно решать такие сложные задачи гигиены и количественной токсикологии, как оценка приемлемых рисков, комбинированного действия химических веществ, обоснование разновременных, региональных, аварийных нормативов и регламентов, комплексного нормативного обеспечения химической безопасности работающих и населения в целом.   Summary   Systematic approach to the hygienic standards of xenobiotics in different environments   M. R. Gzhegotsky, B. M. Shtabsky, L. M. Shafran, W. Zukow   Based on the own experimental data and comprehensive analysis of national toxicometric indicators and MPC of 330 chemicals in different media (working area, atmospheric air and water reservoirs), as well as 265 standards used in the U.S. and the EU, designed and implemented a systematic approach with a purpose to substantiate the chemicals hygienic standards in different media. It takes into consideration the parameters of toxicity and cumulative properties of standardized substances which are manifested integrally by the reliability standard value, determined by the ratio of LC50 (LD50) / MPCwz, which correlates with the corresponding relations of foreign standards. At the same time was justified MPCwz as important system created criteria. The implementation of methodological guide developed by the authors and approved by the Ministry of Public Health of Ukraine provided the opportunity to reduce significantly uncertainties in the process of hygienic standardization, improving the reliability of new developed and correction of existing standards on the basis of newly accumulated experimental and clinical data. Further development of systematic approach to the hygienic standards will more successfully solve challenges of hygiene and quantitative toxicology, as the assessment of acceptable risk, the combined effects of chemical substances, the substantiation of regional, emergency standards, integrated regulatory support of chemical safety of the workers and the population as whole.   Abstrakt (Streszczenie)   Systematyczne podejście do standaryzacji higienicznej ksenobiotyków w różnych środowiskach   M. R. Gzhegotsky, B. M. Shtabsky, L. M. Szafran, W. Zukow   Na podstawie własnych danych doświadczalnych, analiza parametrów krajowych toximetry oraz maksymalne dopuszczalne poziomy 330 substancji chemicznych w różnych środowiskach (strefa robocza, atmosfery i wody) i 265 norm stosowanych w USA i UE, opracowane i realizowane systemowe podejście do obsługuje standardy higieny chemikaliów w różnych mediach.